Diseño de una interfaz usando Python para la identificación de asimetrías temporales en la marcha de personas con prótesis de miembro inferior - Calderón Contreras, Jeysson Alfonso (Universidad Antonio Nariño, 2023)
Lower limb amputations cause irreversible changes and modify the gait cycle, leading to a decrease in the autonomous locomotion capacity of affected individuals. Gait is a synchronous movement of the lower limbs, and any alteration in its determinants results in the concept of asymmetry.